The Nature Of Educators In The Context Of Islamic Education - Abdul Aziz Romdhoni (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
In the context of Islamic education, there are several terms for educators, such as mu'allim, ustadz, murabbi, muyrsid, mudarris, and mu'addib. Each term has a different meaning, depending on the context of the sentence, although in certain situations there are similarities in meaning between them. The word "mu'allim" comes from the verb "allama" in the past tense (madhi) which means "to teach", in the present tense (mudhari) it is "yu'allimu" which means "is teaching", and the isim fa'il (actor) form is "mu'allim" which means "educator". The term "mu'allim" is the most commonly used word and is often found in the hadiths of the Prophet Muhammad. Mu'allim refers to a person who has knowledge and is able to develop it and explain the function of knowledge in life, both theoretically and practically. Mu'allim are also tasked with transferring knowledge, internalizing, and implementing practices.